Corruption Crimes in Indonesia: A Comparative Study - Sumiadi; Laila M Rasyid; Ikramsyah Irwali (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Corruption is an act of deviation that is contrary to the principle of justice (al `adalah). Corruption with all its negative impacts produces various distortions to the life of the state and society can be categorized including fasad actions and cursed by Allah SWT. This research uses a normative approach. The results of this study indicate that in the aspect of Islamic law, there are several types of corruption regulated in Islamic law such as Risywah, Ghulul, Betrayal of trust, Ghasab and Al-Maks or acts of illegal levies. The type of punishment that can be applied to the perpetrators of corruption is ta'zir punishment where the type of punishment is determined by the government (ulil amri) because the sanctions are not explicitly mentioned in the Qur'an and Sunnah. However, in ta'zir punishment, corruptors can be sentenced to death, if the government wants it according to the negative impact of the crime committed.